Analisis Kandungan Nutrisi Berbagai Jenis Makanan Menggunakan Visualisasi Dashboard Interaktif Pada Database USDA : Utilization of Dashboards to Facilitate Nutritional Analysis of Various Food Types - Yafi, Zidni Reynard; Rahim, Abdul; Siswanto, Agus (LPPM Universitas Dinamika Bangsa, 2025)
In today's modern era, awareness of the importance of a healthy diet and balanced nutritional consumption is increasing. However, people are still faced with the problem of a lack of understanding of the nutritional content of various types of food consumed daily. Therefore, an in-depth analysis of the nutritional content of food is an important step to provide accurate information that can be used by individuals, nutritionists, and the food industry. Information about this content can help individuals and institutions, such as nutritionists and the food industry. Nutrition in food plays an important role in maintaining health, this project aims to analyze the nutritional content of various types of food using the USDA (United States Department of Agriculture) database as the main data source. The data is then visualized in the form of an interactive dashboard to facilitate interpretation of the information. In the analysis process, the data is cleaned and processed using structured data management techniques. The results of this analysis are in the form of visualizations that display comparisons of nutritional content between food groups and understand nutritional patterns in more depth.